The link between personal factors and workaholism: The role of remote working during the COVID-19 pandemic - Morkevičiūtė, Modesta; Endriulaitienė, Auksė (Psichologija, 2021)
The aim of the present study was to investigate the role of the way of doing work for the relationship between employees’ perfectionism, type A personality and workaholism during COVID-19 pandemic. A total of 668 Lithuanian employees participated in a study. The sample included employees who worked in the workplace (n = 331), as well as those who worked completely from home (n = 337). The levels of workaholism were measured using DUWAS-10 (Schaufeli et al., 2009). A multidimensional perfectionism scale (Hewitt et al., 1991) was used for the measurement of perfectionism. Type A personality was assessed with the help of the Framingham type A personality scale (Haynes et al., 1980). It was revealed in a study that the positive relationship between perfectionism and workaholism was stronger in the group of complete remote workers. It was further found that the moderating role of the way of doing work was not significant for the relationship between type A personality and workaholism. Overall, the findings support the idea that remote work is an important variable determining the development of health-damaging working behaviors among those employees who excel perfectionistic attributes. Therefore, the way of doing work must be considered when addressing the well-being of employees.